21 Victoria healthy youth survey injury analysis. (9th June 2015) - Matveev, Roman; Macpherson, Alison; Leadbeater, Bonnie
Abstract : Statement of purpose: Injuries in the adolescents are higher than in any other age group and are amongst the leading causes of disability and death. This study aims to identify factors contributing to injury in a population transitioning into adulthood. Methods/approach: Data for this report was drawn from the Victoria Health Youth Survey (VHYS), a random sample, longitudinal study that ran biannually from 2003–2011. Youth aged 14–21 self-reported information on the type, location, cause and other factors associated with the injury. Univariate analysis consisted of t-tests for continuous and X2 for categorical data. Results: In total, 662 individuals participated in 2003, out of which 463 (70%) were available for analysis in 2011. Overall, males were consistently more likely to get injured. As participants got older, they got injured less, were more likely to consume alcohol at the time of injury and tended to take more preventable measures after an injury. Most common types of injuries were sprains/strains and broken bones/bruises. Individuals that exercised frequently were also about 10% more likely to get injured. About 6% of all occurred injuries were concussions. At baseline, most injuries occurred in schools (27%), outside in a park or recreation area (27%) or inside a sports arena/recreation centre (15%). The vast majority of all injuries were unintentional, or non-aggressive in nature (>94%). Conclusions: Drug use, emotional impact, SES, education, average hours of sleep and self-rated physical and mental health did not vary significantly between injured and non-injured participants across the study years. Enhanced knowledge of factors that could influence injury occurrence can improve injury prevention strategies and enhance injury epidemiology research. Significance and contributions: This is one of the few studies to look at injuries in a transitioning, youth population. All of the authors contributed significantly to the design, conception and interpretation of the data.